2007
DOI: 10.2174/157489007779606095
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine, a Partial Fatty Acid Oxidation Inhibitor, its Potential Benefit in Angina and Other Cardiovascular Disorders

Abstract: Chronic Angina resistant to medical treatment with hemodynamically acting agents is a major problem in clinical setup. For such patients, large number of clinical trials have documented the beneficial effect of Ranolazine. It acts as an anti-anginal agent that controls myocardial ischemia through intracellular metabolic changes. Ranolazine is a partial fatty acid oxidation inhibitor which shifts cardiac energy metabolism from fatty acid oxidation to glucose oxidation. Since the oxidation of glucose requires le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
13
0
3
Order By: Relevance
“…Although originally developed to inhibit partial fatty acid oxidation to reduce myocardial oxygen demand (5), ranolazine has a number of pharmacological actions. It is a ␤-adrenergic receptor blocker (18) and an inhibitor of the hERG potassium channel but is best known as a selective inhibitor of the late sodium current (I Na,L ) (3).…”
mentioning
confidence: 99%
“…Although originally developed to inhibit partial fatty acid oxidation to reduce myocardial oxygen demand (5), ranolazine has a number of pharmacological actions. It is a ␤-adrenergic receptor blocker (18) and an inhibitor of the hERG potassium channel but is best known as a selective inhibitor of the late sodium current (I Na,L ) (3).…”
mentioning
confidence: 99%
“…Treatment with GKA50, an activator of glycolysis, resulted in a modest, but significant, reduction in signal intensity. Additionally, HeLa cells were treated with Ranolazine, an activator of pyruvate dehydrogenase and inhibitor of fatty acid beta-oxidation [ 35 ]. Similar to GKA50 treatment, Ranolazine caused a modest, but significant drop in the signal intensity of 18.4 ± 3.3% (mean ± SEM).…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cells were treated with PEG-SOD, PEG-CAT and uric acid [ 59 61 ]. Additionally, HeLa cells were treated with metabolic pharmaceuticals as previously described [ 34 , 35 , 62 ]. All samples were completed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…29,43 In keeping with this logic, previous reports have demonstrated that in myocardial ischaemia, pharmacological modulation of cardiac energy metabolism (how the heart uses glucose or fatty acids as energy) confers cardioprotection mainly because it increases glucose oxidation. 31,44,45 Furthermore, other reports have demonstrated that a shift in cardiac energy substrate utilisation toward glucose oxidation (irrespective of whether cardiomyopathy is from hyperglycaemia or ischaemia) contributes to cardioprotection 43,46 (Figure 1, blue side).…”
Section: Atp Adenosine Triphosphatementioning
confidence: 94%